2019
DOI: 10.3389/fncir.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Role of Striatal Cholinergic Interneurons in Reinforcement Learning From Computational Perspective

Abstract: In this study, we explore the functional role of striatal cholinergic interneurons, hereinafter referred to as tonically active neurons (TANs), via computational modeling; specifically, we investigate the mechanistic relationship between TAN activity and dopamine variations and how changes in this relationship affect reinforcement learning in the striatum. TANs pause their tonic firing activity after excitatory stimuli from thalamic and cortical neurons in response to a sensory event or reward information. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Obviously, it does not prohibit joint operation together with three-factor STDP rules. Interestingly, CIN pause could represent a time window to gate phasic DA release and "bracket" the plasticity window, while DA variations reciprocally modulate the CIN pause duration to adjust this window (Kim, 2019). In the context of reward-based motor adaptation, phasic DA release could thereby deliver reward information for reinforcement learning in a timely manner.…”
Section: Exploring Cholinergic Interneurons Functions In Basal Ganglimentioning
confidence: 99%
“…Obviously, it does not prohibit joint operation together with three-factor STDP rules. Interestingly, CIN pause could represent a time window to gate phasic DA release and "bracket" the plasticity window, while DA variations reciprocally modulate the CIN pause duration to adjust this window (Kim, 2019). In the context of reward-based motor adaptation, phasic DA release could thereby deliver reward information for reinforcement learning in a timely manner.…”
Section: Exploring Cholinergic Interneurons Functions In Basal Ganglimentioning
confidence: 99%
“…We see such data contributing to more accurate description of BG (e.g. [22]) and CB models separately, whereas we tried to use BG and CB models that are as simple as possible and study interactions between them instead.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of ACh, DA release is found to be proportional to the firing rate of DAergic neurons (122). Meanwhile, the computational modeling study of PD showed that the lower DA concentration in turn leads to shortening of CIN activity pause in the striatum, and the phasic DA excursion drives learning (125).…”
Section: Cholinergic Systemmentioning
confidence: 99%